POLITIK IDENTITAS DI INDONESIA: MEMBANGUN SOLIDARITAS ATAU MEMECAH BELAH MASYARAKAT(Upaya Rekonsiliasi Politik Identitas Pasca Pelaksanaan Pemilu 2024) - Sali, Yohanes Mba Malo (Jurnal Studi Ilmu Politik, 2024)
Democratization that defends freedom becomes the basis for every individual to renew themselves, even in political matters. The individual freedoms guaranteed by the Constitution in Indonesia reflect the high popularity of this democratic system. However, this freedom increasingly clarifies the gaps between identities (religion, ethnicity, language and gender) that exist in Indonesia, especially when it comes to national political issues. The identity politics controversy is increasingly heated until a statement of the truth emerges that one interest group is better than another interest group, and this issue of interest begins to divide the nation which has always maintained differences. This article aims to see the extent of the impact of identity politics on Indonesian society by referring to the book Political Philosophy by Armada Riyanto. The methodology used in this article is a qualitative research methodology referring to library research, especially books and articles related to identity politics in Indonesia. The conclusion of this article is that identity politics in Indonesia can destroy the Indonesian state, because there are different groups who demand their freedom.